2020
DOI: 10.1108/jmd-09-2018-0264
|View full text |Cite
|
Sign up to set email alerts
|

Developing leaders through mindfulness practice

Abstract: PurposeThe study's objective was to examine whether and how mindfulness training and practice might impact indicators of three capacities identified as critical for leading in the twenty-first century: resilience, leading in complex contexts and collaboration.Design/methodology/approachWe conducted a non-randomised wait-list controlled study with 57 senior leaders (81 per cent female) who undertook an eight-week “Mindful Leader” programme.FindingsOur findings suggest the programme was effective in developing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 53 publications
(65 reference statements)
1
25
0
4
Order By: Relevance
“…When leaders do so, they can either further expand the benefits of mindfulness for groups who have undergone such training or bring at least some of the benefits of mindfulness to groups that have not. Reitz et al (2020) have shown the value of developing corporate mindfulness programs specifically for leaders. Their study links mindfulness practices to the strategic and human dimensions of leadership.…”
Section: Discussion: Toward a Multilevel Model Of Corporate Mindfulnessmentioning
confidence: 99%
See 1 more Smart Citation
“…When leaders do so, they can either further expand the benefits of mindfulness for groups who have undergone such training or bring at least some of the benefits of mindfulness to groups that have not. Reitz et al (2020) have shown the value of developing corporate mindfulness programs specifically for leaders. Their study links mindfulness practices to the strategic and human dimensions of leadership.…”
Section: Discussion: Toward a Multilevel Model Of Corporate Mindfulnessmentioning
confidence: 99%
“…Reitz et al. (2020) have shown the value of developing corporate mindfulness programs specifically for leaders. Their study links mindfulness practices to the strategic and human dimensions of leadership.…”
Section: Discussion: Toward a Multilevel Model Of Corporate Mindfulnessmentioning
confidence: 99%
“…Fuente: Adaptado de Reitz , Waller, Chaskalson, Olivier, & Rupprecht, 2020;Herda , Cañon , & Young, 2019;Reb, Chaturvedi, Narayanan, & Kudesia, 2019;Yu & Zellmer-Bruhn, 2018;Trowbridge, Lawson, Andrews, Pecora, & Boyd, 2017. En las investigaciones encontradas se puede observar que la decisión de implementar mindfulness en el ámbito laboral, tenía como objetivo introducir la atención plena en el lugar de trabajo, medir el impacto y el efecto que genera en las organizaciones. Otras investigaciones se enfocaron en reducir los niveles de estrés de sus colaboradores e incrementar su eficiencia en el desempeño de funciones.…”
Section: Investigationunclassified
“…The article “Developing leaders through mindfulness practice” by Reitz et al (2020), provides a useful insight into the benefits mindfulness training might have on leadership development. While there has been some doubts about the effects of mindfulness in the past, this article should go to show there are areas where leaders can make genuine progress.…”
Section: Commentmentioning
confidence: 99%